(NiSSLEDOWANIQ o {OPENE(B.s (NmONOGRAFIQs - (Nl(B. (NmAZELXs ((NmOSKWAs (NsOWETSKKII KOMPOZITORs, 1971)
(N| TOM SBORNIK WL@^ENY ^ETYRE RABOTY(B, (NOPUBLIKOWANNYE W RAZNOE WREMQ(B.s
Keywords: (NmONOGRAFIQs